Inspiring effect of lignin on the properties of nanocrystalline cellulose films - Emília Csiszár; Dávid Kun; Fanni Temesváry-Kis; Erika Fekete (Carbohydrate Polymer Technologies and Applications)
The development of cellulose and lignin-based materials is the focus of numerous research projects due to increasing environmental awareness. However, cellulose and lignin cannot be melted or dissolved in their original forms, which limits their utilization. In this study, flexible cellulose nanocrystal (CNC)-lignin films were prepared in a wide composition range. CNC was obtained from bleached flax. The lignin is a by-product of the sulfite pulping. The combination of these materials was prepared and tested for packaging purposes for the first time. Sorbitol and polyethylene glycol plasticizers and an amino-aldehyde crosslinker were also used to improve the properties. The optimum molecular weight of polyethylene glycol is 200 g/mol, as this ensures maximum deformability while the modulus and strength are slightly lower than the plasticizer-free sample. The optimum crosslinker content was found to be 10%, as at this concentration, the best combination of mechanical properties was obtained. CNC hinders the diffusion of oxygen, while the presence of lignin, even in small amounts, significantly improves the UV absorption and thermal stability of the films. With increasing lignin content, modulus and strength deteriorate, but deformability improves. Since the CNC-lignin films are sensitive to water, practical applications can be envisaged in multilayer packaging.